Pengaruh Karakteristik Biografis Terhadap Kinerja Pengrajin Batik Tulis Home Industry Di Desa Paseseh - Iriani Ismail; Yakut Tatin Hamroh (Eco-Entrepreneur, 2021)
The purposes of this study are to identify the biographical characteristics variables which include age, gender, marital status, number of dependents and tenure that affect the performance of the written batik craftsmen in Paseseh village partially and simultaneously. The hypotheses are (1) to determine whether the age variable has a positive and significant effect on the craftsmen's performance (2) to determine whether the gender variable has a positive and significant effect on the craftsmen's performance (3) to determine whether the marital status variable has a positive and significant effect on the craftsmen's performance (4) to determine whether the variable number of dependents has an effect positive and significant impact on the craftsmen's performance (5) to determine whether the variable of tenure has a positive and significant effect on the craftsmen's performance (6) to determine whether the variables of biographical characteristics (age, gender, marital status, number of dependents, and tenure) have a simultaneous effect on the craftsmen's performance.The results of the F test showed that the biographical characteristics (age, gender, marital status, number of dependents, and tenure) have an effect on the craftsmen's performance with the results of Fcount (26.706) Ftable (3.13) and then R Square is 0.641 (64%).Tujuan dari penelitian ini untuk mengidentifikasi variabel karakteristik biografis yang meliputi umur, jenis kelamin, status perkawinan, jumlah tanggungan dan masa kerja mempengaruhi kinerja pengrajin batik tulis di desa Paseseh secara parsial maupun simultan. Hipotesis dalam penelitian ini adalah (1) Variabel umur berpengaruh positif dan signifikan terhadap kinerja pengrajin (2) Variabel jenis kelamin berpengaruh positif dan signifikan terhadap kinerja pengrajin (3) Variabel status perkawinan berpengaruh positif dan signifikan terhadap kinerja pengrajin (4) Variabel jumlah tanggungan berpengaruh positif dan signifikan terhadap kinerja pengrajn (5) Variabel masa kerja berpengaruh positif dan signifikan antara terhadap kinerja pengrajin (6) Variabel karaktertistik biografis (umur, jenis kelamin, status perkawinan, jumlah tanggungan, dan masa kerja) berpengaruh secara simultan terhadap kinerja pengrajin. Hasil dari uji F juga terdapat pengaruh positif dan signifikan antara karaktertistik biografis ( umur, jenis kelamin, status perkawinan, jumlah tanggungan, dan masa kerja berpengaruh terhadap kinerja pengrajin dengan hasil Fhitung (26.706) Ftabel (3,13) dan nilai R Square sebesar 0,641 atau 64%.